Polyelectrolyte films based on chitosan/olive oil and reinforced with cellulose nanocrystals - Pereda, Mariana (2014)
Composite films designed as potentially edible food packaging were prepared by casting film-forming emulsions based on chitosan/glycerol/olive oil containing dispersed cellulose nanocrystals (CNs). The combined use of cellulose nanoparticles and olive oil proved to be an efficient method to reduce the inherently high water vapor permeability of plasticized chitosan films, improving at the same time their tensile behavior. At the same time, it was found that the water solubility slightly decreased as the cellulose content increased, and further decreased with oil addition. Unexpectedly, opacity decreased as cellulose content increased, which balanced the reduced transparency due to lipid addition. Contact angle decreased with CN addition, but increased when olive oil was incorporated. Results from dynamic mechanical tests revealed that all films present two main relaxations that could be ascribed to the glycerol- and chitosan-rich phase, respectively. The response of plasticized chitosan?nanocellulose films (without lipid addition) was also investigated, in order to facilitate the understanding of the effect of both additives.